In vitro anthelmintic effect of Acacia gaumeri, Havardia albicans and Quebracho tannin extracts on a mexican strain of Haemonchus contortus L3 larvae - G. Hernández Orduño (Tropical and Subtropical Agroecosystems, 2008)
The in vitro anthelmintic (AH) effect of Acacia gaumeri (AG), Havardia albicans (HA) and Quebracho tannin extracts on a Mexican strain ofHaemonchus contortus L3 larvae was evaluated.Water/acetone extracts of two tropical plants (AG and HA) and a commercial tannin preparation (Schinopsis sp, Quebracho) were screened to evaluate the in vitro AH effect using the larval migration inhibition (LMI)assay. The Haemonchus contortus L3 larvae originated from a donor sheep (FES-Cuautitlán, UNAM). Theconcentration of condensed tannins in plants extract was 53.9 %, 73.1 % and 55.4% for AG, HA and Quebracho respectively. Clear AH effects wereobtained with HA and Quebracho extracts with different concentrations (600, 1200, 1800 and 2400 µg/ml). Quebracho extract caused a reduction in larval migration which ranged from 15.5 to 25.9% as compared to PBS. The HA extract showed a stronger inhibition effect (30.0 to 53.1%). The AG extract did not inhibit larval migration at the concentrations usedin this trial. These in vitro results suggest that HA have potential AH properties similar to those of Quebracho against a Mexican strain of H. contortus.